THE IMPORTANCE OF CREATING VIRTUAL RESOURCES FROM A MAIN FOREIGN LANGUAGE - Aziza Erbutayeva (International Scientific and Current Research Conferences, 2021)
The introduction of computer technology in the educational process is increasing the interest of students in science. The computer and a number of its programs allow students to better understand the nature of the object, to take an active part in its study, to record the results in programs, to independently change both its parameters and task conditions. At the same time, the teacher's goal is not to transfer basic knowledge in the process of communication with the group, but to improve the electronic recording of the results of laboratory work and practical training, independent work and learning to conduct research. Nowadays, students are learning to record electronically the instructions and concepts given by the teacher during the lesson. Recording programs play an important role in this. They allow you to save any notes and change them at any time, and make it easier for students to record the results of practical work and laboratory work, and enter them into the computer.